A randomized, double-blind study comparing LY2216684 and placebo in the treatment of major depressive disorder - Pangallo, Beth; Dellva, Mary Anne; D’Souza, Deborah N.; Essink, Beal; Russell, James; Goldberger, Celine (Journal of psychiatric research, 2011)
The efficacy, tolerability, and safety of LY2216684, a highly selective norepinephrine reuptake inhibitor, were studied in adult patients with major depressive disorder (MDD). This randomized, double-blind study compared flexible-dose LY2216684 6–18 mg once daily (N = 250) with placebo (N = 245) for 10 weeks acute therapy followed by 1 year LY2216684 treatment (results not reported here). Primary inclusion criteria consisted of GRID 17-item Hamilton Rating Scale for Depression total score ≥18 and Clinical Global Impressions-Severity score ≥4. The primary efficacy measure was the Montgomery-Asberg Depression Rating Scale (MADRS) total score. Response was defined as a ≥50% reduction in MADRS score and remission as MADRS total score ≤10. Global functioning was assessed using the Sheehan Disability Scale (SDS). LY2216684-treated patients showed significant improvement from baseline on the MADRS total score compared with placebo-treated patients (−13.3 vs. −9.8, p < .001), and they had a significantly higher probability of achieving response (49.5%) and remission (29.7%) compared with placebo-treated patients (29.3% and 18.8%, respectively). For the SDS global functional impairment score, LY2216684 treatment resulted in significantly greater improvement compared with placebo treatment (p < .001). More LY2216684-treated than placebo-treated patients discontinued from the study because of an adverse event or death (9.6% vs. 1.6%, p ≤ .001). LY2216684 was associated with significant increases (p < .01) from baseline in systolic (3 mm Hg) and diastolic (4 mm Hg) blood pressure and pulse (10 bpm) compared with placebo. LY2216684 6–18 mg demonstrated significant efficacy and was tolerated in the treatment of MDD.